2002
DOI: 10.1021/bi0255367
|View full text |Cite
|
Sign up to set email alerts
|

Role of Basic Residues of the Autolysis Loop in the Catalytic Function of Factor Xa

Abstract: The autolysis loop of factor Xa (fXa) has four basic residues (Arg(143), Lys(147), Arg(150), and Arg(154)) whose contribution to protease specificity of fXa has not been examined. Here, we substituted these basic residues individually with Ala in the fX cDNA and expressed them in mammalian cells using a novel expression/purification vector system. Following purification to homogeneity and activation by the factor X activator from Russell viper venom, the mutants were characterized with respect to their ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
162
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(170 citation statements)
references
References 42 publications
(74 reference statements)
7
162
1
Order By: Relevance
“…The autolysis loop of fXa contains four basic residues at positions 143, 147, 150, and 154 (Table 1) and the Ala-scanning mutagenesis of these residues has identified Arg-150 as the critical residue that specifically interacts with AT in the presence of pentasaccharide (18). The recent X-ray crystal structure determination of a catalytically inactive mutant of fXa in complex with AT in the presence of pentasaccharide supported the mutagenesis results (26).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The autolysis loop of fXa contains four basic residues at positions 143, 147, 150, and 154 (Table 1) and the Ala-scanning mutagenesis of these residues has identified Arg-150 as the critical residue that specifically interacts with AT in the presence of pentasaccharide (18). The recent X-ray crystal structure determination of a catalytically inactive mutant of fXa in complex with AT in the presence of pentasaccharide supported the mutagenesis results (26).…”
Section: Discussionmentioning
confidence: 76%
“…We investigated the mechanism by which coagulation proteases differentially react with the activated conformation of AT and demonstrated that the autolysis loop of both fXa and fIXa (residues 143-154 in chymotrypsin numbering) (16) have several basic residues that specifically interact with the serpin in the presence of pentasaccharide (17)(18)(19). Thus, we hypothesized that thrombin does not react with the heparin-activated conformation of AT because the basic residues of fXa are not conserved in the autolysis loop of the protease (17).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular modeling suggests that electrostatic fields drive, in part, the interaction of FXa with TFPI (8,9). Basic groups of TFPI would secure contacts within the acidic loop 34 -40 of FXa, whereas an acidic patch may complement the basic autolysis loop of FXa (Arg 143 , His 145 , Lys 148 , and Arg 150 ), even though mutagenesis has failed to confirm its role (53). Compared with FXa, the k a values for E36Q/E37Q/E39Q, E36K/E37K/E39K, E74Q/E76Q/E77Q, and E74K/E76K/E77K inhibition by TFPI decreased 11-, 6-, 3-, and 3-fold, respectively (Table VII).…”
Section: Figmentioning
confidence: 99%
“…and expression of wild-type FX in an expression/purification vector system has been described previously (34). The EGF-N deletion mutant of FX, lacking the exon coding for the N-terminal EGF domain of FX (FX-desEGF-N), was prepared by PCR mutagenesis methods in the same vector system as described (34).…”
Section: Mutagenesis and Expression Of Recombinant Proteins-constructionmentioning
confidence: 99%
“…This mutant was expressed in mammalian cells and purified to homogeneity as described (34). Unlike the previous mutant lacking both the Gla and EGF-N (E2-FX) (31), this mutant contains an intact Gla domain; thus, the zymogenic and enzymatic properties of this mutant could be characterized in appropriate activation complexes on phospholipid vesicles.…”
mentioning
confidence: 99%